PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR TOLAK PELURU GAYA ORTODOKS - Kristina Kristina; Victor G. Simanjuntak; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this study is whether there is an effect of the type of jigsaw cooperative learning model on the ability of orthodox style shotgun learning outcomes in grade VII students of SMP Negeri 12 Pontianak?This research uses an experimental method. The form of research used by researchers is Pre-Experimental Design. The research design used was One Group Pretest-Posttest Design. As for the population in this study were all VII grade students of SMP Negeri 12 Pontianak in the 2018/2019 school year, a total of 93 people. In this study researchers used a sampling technique is a purposive sampling technique. The sample of this study was students of class VII A with a total of 30 people.The significant pretest and posttest values are greater than 0.187 are declared normal.The value of sig 31.00> 0.683 is obtained, then the hypothesis is accepted, meaning that there is an influence of the cooperative learning model of jigsaw type in shot put on the ability of learning outcomes of orthodox style shot put on grade VII students of SMP Negeri 12 Pontianak. Keywords :Cooperative learning, jigsaw, orthodox style bullet resistance learning                  outcomes